Eksplorasi Tumbuhan Pakis di Kebun Raya Indrokilo Boyolali Untuk Pengembangan Multimedia Interaktif Pembelajaran Biologi SMA - Agus Purwanto; Nur Rokhimah Hanik; Suwarto Suwarto (Jurnal Penelitian Pendidikan IPA, 2024)
In today's digital era, conventional learning media has begun to be abandoned. Currently, many modern learning media have been developed such as interactive multimedia, video media, and others so that the learning process becomes fun and students are actively involved in the learning process. The purpose of this study is; to explore the diversity of ferns in the Indrokilo Boyolali Botanical Garden and develop interactive biology multimedia materials for high school. The methods used are field exploration, taxonomic identification, and development of interactive multimedia. The research location is at the Indrokilo Boyolali Botanical Garden and the research was conducted for 3 months starting from December 2022 to February 2023. The results of the research and identification at the Indrokilo Botanical Garden found 31 types of ferns from 14 families and 3 classes. The interactive multimedia developed combines text, images, animations, and interactive videos. This multimedia has been evaluated and received positive validation results, so it can be used as interactive media in high school. Interactive media with other plant samples still needs to be developed because the Indrakilo Botanical Garden is a source of plant diversity